Intravitreal Therapy for Diabetic Macular Edema: An Update - Claudio Furino; Francesco Boscia; Michele Reibaldi; Giovanni Alessio (Journal of Ophthalmology)
Diabetic macular edema (DME) represents a prevalent and disabling eye condition. Despite that DME represents a sight-threatening condition, it is also among the most accessible to treatment. Many different treatment options including photocoagulation, intravitreal medical treatment (either vascular endothelial growth factor inhibitors or corticosteroids therapies), and surgical removal are currently available. Although laser has been considered as the gold standard for many years, over the past several years vascular endothelial growth factor inhibitors (anti-VEGFs) have become first-line therapy. However, many patients do not adequately respond to them. With the development of sustained-release corticosteroid devices, steroids have gained a presence in the management of the DME. We review and update the role of anti-VEGF and intravitreal sustained-release corticosteroid management of DME. According to the currently available scientific evidence, the choice of one anti-VEGF over another critically depends on the baseline best-corrected visual acuity (BCVA). While aflibercept may be the drug of choice in low baseline BCVA, the three anti-VEGFs (bevacizumab, ranibizumab, and aflibercept) provided similar functional outcomes when the baseline BCVA was higher. DEX implants are a valuable option for treating DME, although they are usually seen as a second choice, particularly in those eyes that have an insufficient response to anti-VEGF. The new evidence suggested that, in eyes that did not adequately respond to anti-VEGF, switching to a DEX implant at the time to 3 monthly anti-VEGF injections provided better functional outcomes.